Meningkatkan Aktivitas Berkomentar Melalui Media Pembelajaran Cerita Bergambar Pada Murid Tk Al-Ishaq Al-Patue Kabupaten Bone - hamri hamri (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2019)
This study aims to improve: (1) Student learning activeness, (2) understanding teaching material, (3) students' independent learning independence, (4) improving student learning outcomes and the independence of TK Al-Ishaq Al-Patue students during the learning process with the media comic. The subjects of the action recipients were students of group A TK Al-Ishaq Al-Patue which amounted to 16 students, the subject of action was researchers and subjects who helped implementers were kindergarten teachers Al-Ishaq Al-Patue and the principal. Data is collected through observation, field notes, reviews, and documentation. Qualitative descriptive data analysis with percentage and model flow. The results of this class action research are first, collaborative work developed can improve the understanding of Kindergarten Teacher Al-Ishaq Al-Patue, about, (1) problems that arise in the classroom, (2) ways of collaborative work to develop a learning improvement plan . Second, collaborative work successfully implements learning planning well, (1) can change conventional learning activities into learning approaches through the provision of the pictorial stories, (2) can change passive learning activities into active, creative and interactive learning, (3) on every learning always pays attention to aspects of learning. Third, with the application of learning through the presentation of pictorial story approaches there was an increase in students 'commenting skills, namely completeness in cycle I 56.25%, even in cycle II students' completeness had reached 87.50%, which meant that there was a significant increase after learning models were given.